Kolaborasi Guru dalam Mendesain Pembelajaran Melalui Praktik Lesson Study for Learning Community di SMK Pembangunan Ternate - Endang Purwati; Kapraja Sangadji (Peneliti.net, 2020)
This study aims to uncover learning lessons that are able to build a culture of collaboration in improving the quality of learning in the classroom. This study uses qualitative research with case study type. Data collection techniques are done by interview and observation. The subjects of this study were all teachers who were in charge of normative, adaptive and productive subjects involved in school-based learning. The findings in this study indicate two conclusions. First, it is the teacher who receives positive learning in improving the quality of learning in each class through the collaboration of fellow teachers in designing learning. Secondly, through this collaboration, a culture of learning to grow and develop together began to form between the teachers